An assessment of Body Mass Index and sensitive period for overweight development in Macao students at primary school age - King Yan Ho, Walter; Ahmed, Md. Dilsad; Leong, Chi Ian; Chan, Patrick; Van Niekerk, Rudolph Leon; Huang, Fan; Chen, Jessica; Chan, Nikon; Silva, João; Ip, Patrick (Anthropological Review, 2019)
The concomitant risk of physical inactivity and sedentary lifestyle development causing various non-communicable diseases is recognized worldwide. Therefore, development of strategies to form a concrete public health policy overcoming this problem is most important. This study observed the distribution and changes of Body Mass Index (BMI) over six years among boys and girls. Data on children height and weight and their BMI were collected. A total of 5369 (3368 male and 2001 female) children were recruited from 10 schools in Macao. The children were 6 years old in 2008 and turned 11 in 2013. Statistical analyses involved descriptive statistics, t-test, and a Chi-squared test. The findings indicated greater BMI among males than females across all age at the 0.05 level of significance, and the ages of 8 and 9 seemed to be a sensitive period for an increase in overweight and obesity. The results indicate the need to have focused strategies and structured interventions for males at the critical ages from 8 to 9 years.